2019
DOI: 10.1038/s41598-019-50877-8
|View full text |Cite
|
Sign up to set email alerts
|

TFEB activates Nrf2 by repressing its E3 ubiquitin ligase DCAF11 and promoting phosphorylation of p62

Abstract: Transcriptional factor EB (TFEB) and nuclear factor E2-related factor 2 (Nrf2) play crucial roles in the biological response against cellular stressors; however, their relationship has not yet been investigated. Here, we constructed human neuroglioma cell lines stably expressing TFEB. The expression of Nrf2-response genes, including heme oxygenase (HO)-1, glutathione-s-transferase-mu1 (GSTM1), and p62, was induced in the cell line, independent of oxidative stress. Of note, the protein level of Nrf2 was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…Importantly, the p62 S351 is phosphorylated in selective autophagy conditions such as impaired proteostasis, mitochondrial depolarization, and bacterial infection 21 , 46 , 47 . In a previous study, we observed increased phosphorylation of p62 at S351 in addition to Nrf2 activation in TFEB-expressing cells 48 . Thus, the Keap1-Nrf2 pathway and selective autophagy, the major stress response pathways, are coupled to each other via the phosphorylation of p62 17 .…”
Section: Discussionmentioning
confidence: 69%
“…Importantly, the p62 S351 is phosphorylated in selective autophagy conditions such as impaired proteostasis, mitochondrial depolarization, and bacterial infection 21 , 46 , 47 . In a previous study, we observed increased phosphorylation of p62 at S351 in addition to Nrf2 activation in TFEB-expressing cells 48 . Thus, the Keap1-Nrf2 pathway and selective autophagy, the major stress response pathways, are coupled to each other via the phosphorylation of p62 17 .…”
Section: Discussionmentioning
confidence: 69%
“…These studies highlight the crucial role of Nrf2 in regulating mitophagy in DKD. A recent study by Park et al (2019) suggests that novel regulation of Nrf2 by TFEB mitigates oxidative stress. Interestingly, the activities of both Nrf2 and TFEB were shown to be downregulated in DKD (Xiao et al, 2017;Zhao et al, 2018).…”
Section: Mitophagy and Dkdmentioning
confidence: 99%
“…Several cysteine residues in KEAP1 can be oxidised leading to conformational changes and thereby preventing NRF2 degradation [ 342 ]. In addition, p62/SQSTM1 also binds to KEAP1, marking it for degradation; meanwhile, TFEB represses the NRF2-ubiquitin ligase, DCAF11 (DDB1- and CUL4-associated factor 11)), ultimately promoting NRF2 translocation to the nucleus [ 343 , 344 ] to establish a feed-forward loop. Finally, there is some evidence indicating that NRF2 is also subject to redox cysteine modifications, promoting NRF2 nuclear translocation; consistent with this, mutations in these cysteines enhance interactions with KEAP1, thus increasing NRF2 degradation [ 345 ].…”
Section: Autophagy and Redoxtasis Crosstalkmentioning
confidence: 99%